Measuring the quality level of the actual performance of university office services From the viewpoint of students of some of the universi bin Bolai -Batna 2.ty libraries Mustafa - attoui, nassira; baiben, nadia (Journal of Social Sciences and Humanities, 2022)
This study aims to identify the quality of university office services through the use of a measure of the quality of actual service performance) SERVPERF( It is designed to measure the quality of the actual performance that the beneficiary understands In light of the five main dimensions that are the quality of service. which is(Tangibility, reliability, responsiveness, safety, empathy) Where a sample of(110) A student from some of the university libraries Batna 2 - Mustafa bin Bo laid. Forms were randomly distributed to them. The descriptive approach was adopted to suit the topic, and in the analysis of the results, statistical methods, standard deviations, and the T-test. The results of this study concluded that the level of quality of services provided and perceived by the students of libraries is low Also, there were no differences between the level of evaluation of the quality of office. services by removing the ServParf scale from the students' viewpoint due to the academic level.